Splenic Tuberculosis: A Cause of Pyrexia of Unknown Origin Report of Two Cases - Kabir, Ahmedul; Das, Aparna; Banna, Mahmudul Hassan; Minnat, Baharul; Ahasan, H A M Nazmul (Journal of Medicine, 2013)
Tuberculosis of spleen is an extremely rare clinical entity. It often poses diagnostic difficulties as microbiological confirmation of diagnosis is not easy. We encountered two casas who presented with prolong fever but no other symptoms. Laboratory data provided no specific information for diagnosis. Abdominal ultrasonography revealed splenomegaly with multiple small hypoechoic lesions within the spleen. A diagnosis of isolated splenic tuberculosis was confirmed after a splenic puncture and histopathological examination. DOI: http://dx.doi.org/10.3329/jom.v14i1.14586 J MEDICINE 2013; 14 : 88-90